Mucocutaneous Lymph Node Syndrome - Rusdi Ismail; Dahler Bahrun; Sawitri Sjaffar (Paediatrica Indonesiana, 1979)
A case of Mucocutaneous Lymph Node Syndrome in a 12-year-old girl of Chinese parentage has been reported. This was the first case of MLNS reported from Indonesia.